Desempenho dinâmico de um trator agrícola utilizando biodiesel destilado de óleo residual - Soranso, Ana M.; Gabriel Filho, Antonio; Lopes, Afonso [UNESP]; De Souza, Eduardo G.; Dabdoub, Miguel J.; Furlani, Carlos E. A. [UNESP]; Da Camara, Felipe T. [UNESP] (FapUNIFESP (SciELO), 2008)
The objective of this study was to evaluate the dynamic performance of an agricultural tractor utilizing distilled biodiesel (50% ethylic + 50% methylic) as a function of the proportion of biodiesel and diesel of petroleum (0 and 100%, 5 and 95%, 15 and 85%, 25 and 75%, 50 and 50%, 75 and 25% and 100 and 0%), respectively. This research was done in the area of the Department of Rural Engineering of the Paulista State University (UNESP), Jaboticabal Campus, SP, located in the latitude 21° 14′ 28″ S and longitude 48° 17′12″ W. A tractor 4 x 2 FWA was used, with a 73.6 kW (100 HP) motor and a ballast tractor. The biodiesel used was produced from spent oil from food frying. The experimental design was entirely randomized, with 7 treatments and 5 repetitions, totaling 35 observations. The results showed that the biodiesel and diesel blend significantly influenced the hourly volumetric consumption, hourly mass consumption, fuel consumption per worked area and specific fuel consumption variables. When the tractor operated with 100% of biodiesel (B100) the specific fuel consumption increased 18% on average in relation to diesel (B0).
Dynamic performance of an agricultural tractor utilizing distilled biodiesel from spent oil
Keywords: Biofuel; Blend of fuels; Fuel consumption